Increasing Environment Productivity of Crispy Fried Chicken Vendors Using the Green Productivity Method: Peningkatan Produktivitas Lingkungan pada Penjual Ayam Goreng Crispy Menggunakan Metode Green Productivity - Apriliana Sari, Indah; Marodiyah, Inggit; Hanun, Nur Ravita (Universitas Muhammadiyah Sidoarjo, 2022)
Cooking oil is one of basic needed for food vendors especially crispy chicken (CC). The CC vendors will use a large amount of cooking oil. The frying oil are usually composed clean oil and flour slurry. The habit that often done by seller CC are reuse the frying oil which still clear, and throw the sediment (flour slurry) in the trash or river. Of course, that will be one caused damage of environment surrounding. Purpose this research are to identifying the management of waste fried oil and flour slurry. The investment cost of preventing environmental impact and the benefits which they were obtain, be the problem that have not been mitigation of environmental impact yet. In this research, applied the Green Productivity Method to provide mitigation environmental impact from waste cooking oil.